Spatial and temporal drivers of fluorescence quantum yield variability in the Southern Ocean. Issue 3 (4th January 2023) - Ryan‐Keogh, Thomas James; Bone, Emma Lewis; Thomalla, Sandy J.; Lain, Lisl; Smith, Marie E.; Bernard, Stewart; Vichi, Marcello
Abstract: Fluorescence quantum yield is a powerful tool for assessing phytoplankton photophysiology and photosynthetic efficiency, but there is a paucity of in situ studies. Here we present the first wavelength‐specific fluorescence quantum yield data from high spatial and temporal resolution real‐time measurements made in the Southern Ocean. This dataset represents both winter and summer conditions across a broad latitudinal range of the Atlantic and Indian South Ocean and the presented analysis assesses the potential influence of a range of physical, chemical, and biological drivers of variability. The results indicate that both light history and potential iron limitation play significant roles in constraining the magnitude of fluorescence quantum yield on a seasonal basis, with links to specific pigment composition of carotenoids involved in fluorescence quenching. Whereas community structure and associated pigment content play a strong role in dictating the spectral shape of fluorescence quantum yield both seasonally and spatially, with larger diatom‐dominated communities fluorescing more in the blue region of the spectrum and smaller phycoerythrin‐containing phytoplankton fluorescing more in the green‐orange region of the spectrum. This study provides a better understanding of the drivers of variability of in situ fluorescence quantum yield, which is useful for informing interpretations of studies based on remotely sensed signals, which are essential for investigating spatial and temporal variability in photophysiological characteristics on longer time scales.